Non-classical monocyte levels correlate negatively with HIV-associated cerebral small vessel disease and cognitive performance - Singh, Meera V.; Uddin, Md Nasir; Covacevich Vidalle, Mae; Sutton, Karli R.; Boodoo, Zachary D.; Peterson, Angelique N.; Tyrell, Alicia; Tivarus, Madalina E.; Wang, Henry Z.; Sahin, Bogachan; Zhong, Jianhui; Weber, Miriam T.; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundDespite antiretroviral treatment (cART), aging people living with HIV (PWH) are more susceptible to neurocognitive impairment (NCI) probably due to synergistic/additive contribution of traditional cerebrovascular risk factors. Specifically, transmigration of inflammatory CD16+ monocytes through the altered blood brain barrier (BBB) may exacerbate cerebral small vessel disease (CSVD), a known cause of vascular cognitive impairment.MethodsPWH on cART (n=108) and age, sex, and Reynold’s cardiovascular risk score-matched uninfected individuals (PWoH, n=111) were enrolled. This is a longitudinal observational study but only cross-sectional data from entry visit are reported. Neuropsychological testing and brain magnetic resonance imaging (MRI) were performed. CSVD was diagnosed by Fazekas score ≥1. Flow cytometric analyses of fresh whole blood were conducted to evaluate circulating levels of monocyte subsets (classical, intermediate, and non-classical) and markers of monocyte activation (CCR2, CD40, PSGL-1, TNFR2 and tissue factor). ELISAs were used to measure sCD14, ICAM, and Osteoprotegerin. Two-way analysis of variance (ANOVA), and linear regression models were performed to study the effects of HIV status, CSVD status, and their interaction to outcome variables such as cognitive score. Two-sample t-tests and correlation analyses were performed between and within PWoH with CSVD and PWH with CSVD participants.ResultsPWH with CSVD (n=81) had significantly lower total cognitive scores, higher levels of NCMs and soluble CD14 and intracellular adhesion molecule 1 (ICAM-1) as compared to PWoH with CSVD group (n=68). sCD14 and ICAM1 were positively correlated with each other indicating that monocyte and endothelial activation are associated with each other. Cognition was negatively correlated with NCMs, especially in the PWH with CSVD group. Among other blood biomarkers measured, osteoprotegerin levels showed mild negative correlation with cognitive performance in individuals with CSVD irrespective of HIV status.ConclusionsElevated levels of NCMs may contribute to neuroinflammation, CSVD and subsequent cognitive impairment. This finding is of particular relevance in aging PWH as both HIV and aging are associated with increased levels of NCMs. NCMs may serve as a potential biomarker to address these comorbidities. Further longitudinal studies are needed to evaluate whether changes in NCM levels are associated with changes in CSVD burden and cognitive impairment.